2009
DOI: 10.1002/mawe.200800412
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the resorbable magnesium . alloys LAE442 und MgCa0.8 concerning their mechanical properties, their progress of degradation and the bone‐implant‐contact after 12 months implantation duration in a rabbit model

Abstract: Extruded implants (2.5 mm x 25 mm) of the resorbable magnesium alloys MgCa0.8 and LAE442 were implanted into the marrow cavity of both tibiae of 10 New Zealand White rabbits. The animals were in a good general condition over the whole experimental period and showed no signs of lameness. Radiographic examinations could not reveal any generation of gas. The endosteal based bone adhesion to the implant surface was evaluated by l-computed tomography of the right tibia. 53 % of the evaluated slices of the alloy LAE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
131
2
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 15 publications
4
131
2
1
Order By: Relevance
“…A high corrosion rate results in gas formation and a rapid loss of mechanical strength [12] . In vivo models are essential for evaluating magnesium alloys as an implant material, because in vivo and in vitro corrosion rates can differ to a large extent [3,13] .…”
Section: Introductionmentioning
confidence: 99%
“…A high corrosion rate results in gas formation and a rapid loss of mechanical strength [12] . In vivo models are essential for evaluating magnesium alloys as an implant material, because in vivo and in vitro corrosion rates can differ to a large extent [3,13] .…”
Section: Introductionmentioning
confidence: 99%
“…1,25 Several studies have investigated the properties and corrosion behavior of binary magnesium-calcium alloys. 13,14,18,19,[26][27][28][29][30] The addition of calcium provides solid solution strengthening and contributes to grain refinement owing to grain boundary strengthening. 1 It was observed that the addition of calcium above the solubility limit of approximately 1.34 wt% Ca enhanced the corrosion rate.…”
Section: Introductionmentioning
confidence: 99%
“…18 Previous studies have demonstrated good biocompatibility of MgCa0.8 in vivo. 13,28 The production of high amounts of gas in a short time due to high corrosion rates is undesirable for clinical applications. The accumulation of gas associated with MgCa0.8 implants was mild to moderate in vivo, with no harmful effects toward the animal.…”
Section: Introductionmentioning
confidence: 99%
“…In general anaesthesia, a hole was drilled into the tibial plateau and the implant was inserted. The detailed operation procedure is described elsewhere (Thomann et al, 2009). Radiographs of two planes were taken immediately after surgery (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In µ-computed tomography, samples were analysed with a slice sickness of 36µm and a scanning time of 1s. An evaluation of endosteal and periosteal bone remodeling as well as bone adhesion on the implant material was done with a semi quantitative scoring system (Krause et al, 2010; Thomann et al, 2009) (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%